MODAL SOSIO-POLITIK KEMENANGAN CALEG PEREMPUAN PADA PEMILU 2024 (Studi Kasus atas Terpilihnya Maria Roswita Mea Laki di Dapil III Nagekeo) - Febronius Yano; Didimus Dedi Dhosa; Yohana Fransiska Medho (Journal Education and Government Wiyata, 2025)
This research is titled The Socio-Political Capital Behind the Victory of Female Legislative Candidates in the 2024 Election: A Case Study of Maria Roswita Mea Laki’s Election in Electoral District III, Nagekeo." The research problem addressed in this thesis is: "What are the socio-political capitals of female legislative candidates in the 2024 election, as evidenced by the case of Maria Roswita Mea Laki’s election in Electoral District III, Nagekeo. Theories used to address the research problem include political capital, social capital, and economic capital. Primary data sources consist of interviews with informants, while secondary data sources comprise documents related to the research variables. Data collection methods include interviews, observations, and documentation. The data analysis process involved data reduction, data presentation, and conclusion drawing, analyzed using a descriptive qualitative approach. The research findings indicate the following : 1) Political Capital: The strategic support of the mosalaki (respected traditional leaders) played a pivotal role in Maria Roswita Mea Laki’s victory in the 2024 legislative election in Electoral District III, Nagekeo. The mosalaki not only provided traditional legitimacy that strengthened public acceptance but also actively organized support through traditional gatherings, direct communication, and culturally significant campaign facilities. This role, complemented by a solid and inclusive campaign team, successfully reached various community segments through cultural approaches, social activities, and direct interactions. By fostering emotional bonds and public trust, Maria Roswita’s campaign became a means of reinforcing traditional values while realizing shared aspirations, culminating in a significant victory. 2) Social Capital: Maria Roswita Mea Laki's social capital was largely influenced by her father, Urbanus Laki, a well-respected figure with strong social ties through traditional, social, and youth activities. His active involvement with community groups, such as mosalaki, the Hobonaku Farmers Group, and the Pelopor FC football club, further solidified public trust and broadened support for Maria Roswita’s candidacy. 3) Economic Capital: The financial support of IDR 400 million provided by Urbanus Laki facilitated an organized and effective campaign. This funding enabled the production of campaign materials such as billboards, posters, and banners, the provision of transportation for voters in remote areas, and the organization of well-supported face-to-face meetings. These efforts not only expanded voter reach but also strengthened emotional connections between Maria Roswita and the community, enhancing voter trust in her commitment to their aspirations. Based on the analysis, the author concludes that Maria Roswita Mea Laki’s victory in Electoral District III, Nagekeo, in the 2024 legislative election was significantly influenced by her political, social, and economic capital.